Different Phenotypes of Osteoarthritis in the Lumbar Spine Reflected by Demographic and Clinical Characteristics: The Johnston County Osteoarthritis Project. Issue 7 (11th June 2020) - Goode, Adam P.; Cleveland, Rebecca J.; George, Steven Z.; Kraus, Virginia B.; Schwartz, Todd A.; Gracely, Richard H.; Jordan, Joanne M.; Golightly, Yvonne M.
Abstract : Objective: To determine if associations between demographic and clinical characteristics and appendicular joint osteoarthritis (OA) reflect different phenotypes of OA in the lumbar spine. Methods: Participants were from the Johnston County OA Project. Demographic information consisted of age, sex, and race (white and African American), and clinical characteristics consisted of body mass index (BMI), low back pain and injury, and knee, hip, and hand OA. Participants were categorized as having spine OA, facet joint OA, both spine OA and facet joint OA, or neither spine OA nor facet joint OA (referent group). Multinomial regression models were used to determine odds ratios (ORs) and 95% confidence intervals (95% CIs). Results: Of 1, 793 participants, the mean ± SD age was 66.2 ± 10.1 years, and the mean ± SD BMI was 30.7 ± 6.2. The majority of the participants were women (n = 1, 144 [63.8%]), and 31.8% of the participants (n = 570) were African American. Eighteen percent of participants had neither spine OA nor facet joint OA, 22.8% had facet joint OA, 13.2% had spine OA, and 46.0% had both spine OA and facet joint OA. In adjusted analyses, African Americans were less likely to have facet joint OA (OR 0.68 [95% CI 0.49–0.95]) or both spine OA and facet joint OA (OR 0.51 [95% CI 0.37–0.70]). Women were more likely to have facet joint OA (OR 1.71 [95% CI 1.24–2.36]). Having a BMI of ≥30 was associated with having facet joint OA (OR 1.76 [95% CI 1.28–2.42]) and both spine OA and facet joint OA (OR 1.85 [95% CI 1.37–2.51]). Knee OA was associated with all 3 OA groups, while lower back injury was associated only with those with spine OA. Participants with hip OA were less likely to have facet joint OA. Conclusion: Race, sex, BMI, hip OA, and lower back injury may help identify different OA phenotypes in the lumbar spine.